Upregulation of the p53-p21 pathway by G2019S LRRK2 contributes to the cellular senescence and accumulation of α-synuclein. Issue 4 (16th February 2019) - Ho, Dong Hwan; Seol, Wongi; Son, Ilhong
ABSTRACT: Parkinson's disease (PD) is characterized by the degeneration of dopaminergic neurons in the substantia nigra and the presence of Lewy bodies (LB) in neurons. α-Synuclein (αSyn) is a major component of LB and promote the PD pathogenesis via its accumulation by the impaired proteasomal or autophagic clearance. Numerous studies have revealed that the reduction of proteasome activity and autophagy is accelerated by cellular senescence. Leucine-rich repeat kinase 2 (LRRK2) contributes to PD progression and its most prevalent mutation, G2019S LRRK2, increases its activity. Our previous report has shown that the G2019S LRRK2 mutant promoted p53-induced p21 expression and neuronal cytotoxicity. The p53-p21 pathway plays a role in cellular senescence. We hypothesized that the loss of dopaminergic neurons by the stimulated p53-p21 pathway via the G2019S LRRK2 mutation might be associated with cellular senescence, thereby promoting the accumulation of αSyn. We confirmed that the ectopic expression of the phosphomimetic p53 mutant, p21, or G2019 in differentiated SH-SY5Y cells increased the following: 1) the expression of β-galactosidase, a marker of cellular senescence, and the activity of senescence-associated β-galactosidase, 2) endogenous αSyn protein level, but not its mRNA level, and 3) αSyn fibril accumulation in dSH-SY5Y via low proteasome and cathepsin D activities. Elevated oligomeric αSyn and the increase in β-galactosidase with induced p21 were observed in brain lysates of G2019S transgenic mice. Our results suggest that cellular senescence is promoted via the p53-p21 pathway due to the G2019S LRRK2 mutation. Eventually, decreased protein degradation by G2019S-mediated senescence could accelerate αSyn aggregate formation.